Perioperative analgesic effects of an ultrasound-guided transversus abdominis plane block using bupivacaine in goats undergoing celiotomy - Morris, Tate B.; Hopster, Klaus; Fecteau, Marie-Eve (Frontiers in Veterinary Science, 2023)
Introduction Never has the anatomy, the procedure of the transversus abdominis plane (TAP) block, or the perioperative analgesic effects of a bupivacaine TAP block been described in goats. Methods This report details the relevant anatomy in a cadaveric study combined with the description/use of a TAP block in a controlled, randomized, prospective, blinded clinical study in which 20 goats with urolithiasis presenting for either ventral midline or paramedian celiotomy were enrolled. Anesthesia was induced with ketamine and midazolam and maintained with desflurane in oxygen. An ultrasound-guided TAP block was performed using 0.25% bupivacaine (4 sites, 0.4 mL/kg each site) (bupivacaine-TAP, n = 10) or equal volume of saline (control-TAP, n = 10). When indicated, urethral amputation was performed followed by celiotomy with cystotomy or tube cystostomy. Urethrotomy was performed if warranted. Intraoperatively, a 20% increase in mean arterial pressure (MAP), heart rate (HR) and/or respiratory frequency was treated with an increase in desflurane concentration of 0.5 Vol.%. Goats received ketamine boluses (0.2 mg/kg IV) when moving spontaneously. At 2, 12, and 24 h post-extubation, pain was scored with a descriptive scale. Data were analyzed with an analysis of variance (ANOVA) or the Wilcoxon signed-rank test, and P < 0.05 was considered statistically significant. Results Bupivacaine-TAP goats exhibited lower end-tidal desflurane concentration requirements (P = 0.03), lower pain scores at 2-h post-extubation (P = 0.02), shorter anesthetic recovery times (P = 0.03) and decreased HR and MAP during surgical stimulation. Goats receiving a bupivacaine TAP block experienced less intraoperative nociceptive input requiring less inhalant anesthetic leading to faster anesthetic recoveries and decreased postoperative pain. Discussion Ultrasound-guided TAP block is a simple technique to decrease anesthetic requirement while providing additional postoperative comfort in goats undergoing celiotomy.